Development and characterization of milkfish (Chanos chanos) burger patty - Pitogo, Bianca Celeste Lavilla (2009.)
A burger patty from lean milkfish meat was developed and characterized.
Thesis (Undergraduate. Bachelor of Science in Food Technology)School of Technology, University of the Philippines in the Visayas.
Keywords: Milkfish; Chanos chanos; Burger patty